2007
DOI: 10.1590/s1413-78522007000400011
|View full text |Cite
|
Sign up to set email alerts
|

Dores na coluna: avaliação em pacientes com hipertrofia mamária

Abstract: OBJETIVO: Avaliar a influência da hipertrofia mamária sobre as dores na coluna e o quanto poderão comprometer as atividades habituais das pacientes. MÉTODOS: Realizou-se estudo transversal analítico em pacientes dos ambulatórios de Ortopedia e Cirurgia Plástica do Hospital Universitário Samuel Libânio, Pouso Alegre - MG. Foram examinadas 100 mulheres, 50 com hipertrofia mamária (grupo estudo) e 50 com mamas normais (grupo controle). O tamanho das mamas foi classificado conforme critérios de Sacchini.. A Escala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 11 publications
(22 reference statements)
1
2
0
2
Order By: Relevance
“…Pretest results with high levels of back pain or discomfort were also observed by Fernandes et al (4), who used a numerical scale to assess pain intensity ranging from 0 to 10, and reported mean pain values of 5.5, 6.5 and 6.2 for the cervical, thoracic and lumbar spines, respectively. Benditte-Klepetko et al (10) showed a positive correlation between breast weight and back pain, even when age and BMI were controlled for.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Pretest results with high levels of back pain or discomfort were also observed by Fernandes et al (4), who used a numerical scale to assess pain intensity ranging from 0 to 10, and reported mean pain values of 5.5, 6.5 and 6.2 for the cervical, thoracic and lumbar spines, respectively. Benditte-Klepetko et al (10) showed a positive correlation between breast weight and back pain, even when age and BMI were controlled for.…”
Section: Discussionsupporting
confidence: 67%
“…Regarding the anthropometric variables, there were no significant differences in body mass and BMI after surgery, indicating that despite breast mass reduction, women retained their body mass and BMI. This was probably due to the recovery period, in which patients stayed home and avoided upper limb movements, which led to lower energy expenditure and, (4,11,14) have also verified higher BMI values in women with breast hypertrophy.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…A utilização dos questionários padronizados Roland-Morris e SF-36 possibilitaram avaliar a qualidade de vida dos pacientes através de suas próprias perspectivas 12 , pois são questionários auto-aplicativos, no qual o paciente fez suas escolhas de respostas.…”
unclassified
“…Fernandes et al mostraram que dores nas costas são mais intensas e determinaram maior limitação das atividades habituais em pacientes portadoras de hipertrofia mamária (47) . A qualidade de vida e a função pós-operatória em pacientes submetidos à artroplastia de Girdlestone, na população brasileira, ainda necessitam ser mais pesquisadas, pois os resultados são indicações do comportamento das variáveis de estudo e não podem ser consideradas encerradas (48) . A versão em português do Questionário de Claudicação de Edimburgo manteve níveis adequados de sensibilidade e especificidade, podendo ser recomendado para o rastreamento de doença arterial obstrutiva na prática clínica e em estudos epidemiológicos realizados no Brasil (49) .…”
Section: Ortopediaunclassified